2008
DOI: 10.1016/j.evalprogplan.2007.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Ten years later: Locating and interviewing children of drug abusers

Abstract: Longitudinal studies require high follow-up rates in order to maintain statistical power, reduce bias, and enhance the generalizability of results. This study reports on locating and survey completion for a 10-year follow-up of the Focus on Families project, an investigation of 130 families headed by parents who were enrolled in methadone treatment for opiate addiction. Despite having no contact with participants in the study for at least 10 years, the project successfully located nearly 99% of parent particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(48 citation statements)
references
References 24 publications
2
44
2
Order By: Relevance
“…Fernandez (2008) followed up children in permanent foster care (a 'captive' population from a research point of view) and McAuley and Trew (2000) followed up other foster children over a very short period of time (one year). Tracing respondents after a considerable amount of time has passed between baseline and follow-up does, however, have a history in other fields, particularly in epidemiological and public health research (Hser et al 2001;Lyons et al, 2004,) where successful tracing of respondents is considered crucial to reduce study bias and increase study power (Haggerty et al, 2008;Wutzke et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fernandez (2008) followed up children in permanent foster care (a 'captive' population from a research point of view) and McAuley and Trew (2000) followed up other foster children over a very short period of time (one year). Tracing respondents after a considerable amount of time has passed between baseline and follow-up does, however, have a history in other fields, particularly in epidemiological and public health research (Hser et al 2001;Lyons et al, 2004,) where successful tracing of respondents is considered crucial to reduce study bias and increase study power (Haggerty et al, 2008;Wutzke et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Weinberger et al (2002) attempted to trace 708 people who had participated in clinical studies 27 years previously and found 84%, despite having no contact with study participants in the intervening years. Wilson et al (2009) traced 70.1% of 810 individuals who were treated for cancer during childhood in Sydney and Haggerty et al (2008) completed a 10-year follow-up of 130 methadone patients and their families, finding 99% of subjects. Boice (1978) found 93% of 1764 former sanitorium patients and Rodger et al (2001) traced a sample of patients (including injecting drug users) 25 years after they were treated and found 66% of them.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, research teams may need to assist participants with locating computer and web access when participants are mobile. As always, research teams need to be patient, persistent, and creative to achieve high follow-up rates [49][50][51].…”
Section: Discussionmentioning
confidence: 99%
“…While most longitudinal studies, sometimes also called panel or follow-up studies, are prospectively planned and have a definitive end date, there has been a recent resurgence in reconstituting "dormant" longitudinal or even cross-sectional studies (e.g., Haggerty et al 2008;Hampson et al 2001;Hauser 2005;Kimmel and Miller 2008;Ortiz and Godinez Ballon 2007). One reason for this resurgence is the higher costs associated with conducting new longitudinal studies relative to repurposing or continuing preexisting ones.…”
Section: Introductionmentioning
confidence: 99%
“…What have we learned? Certain subgroups are more difficult and expensive to find because they require more complex tracking steps: females, minorities, and individuals with lower educational attainment, higher rates of financial instability, and criminal behavior or substance abuse (Andresen et al 2008;Cotter et al 2005;Cottler et al 1996;Haggerty et al 2008;Iannacchione 2003;Jessor and Jessor 1977;Passetti et al 2000;Ribisl et al 1996;Stouthamer-Loeber and van Kammen 1995).…”
Section: Introductionmentioning
confidence: 99%